Short-term binge drinking, marijuana, and recreational drug use trajectories in a prospective cohort of people living with HIV at the start of COVID-19 mitigation efforts in the United States. (1st February 2022) - Meanley, Steven; Choi, Seul Ki; Thompson, Azure B.; Meyers, Jacquelyn L.; D'Souza, Gypsyamber; Adimora, Adaora A.; Mimiaga, Matthew J.; Kempf, Mirjam-Colette; Konkle-Parker, Deborah; Cohen, Mardge H.; Teplin, Linda A.; Murchison, Lynn; et al.
Abstract: Background: At the start of the COVID-19 pandemic, HIV experts suggested that an increase in mental health diagnoses and substance use among people living with HIV (PLHIV) may be an unintended consequence of COVID-19 mitigation efforts (e.g., limiting social contact). We evaluated short-term trajectories in binge drinking, marijuana, and recreational drug use in a prospective cohort of PLHIV. Methods: Data ( N = 2121 PLHIV) consist of survey responses on substance use behaviors from two pre-COVID-19 (October 2018-September 2019) and one COVID-19-era (April 2020-September 2020) timepoints within the MACS/WIHS Combined Cohort Study (MWCCS). We conducted group-based trajectory models, triangulated with generalized linear mixed models, to assess changes in binge drinking, daily marijuana use, and recreational drug use at the start of the pandemic. Controlling for age and race/ethnicity, we tested whether trajectories differed by sex and early-pandemic depressive symptoms, loneliness, and social support. Results: Group-based trajectory models yielded two trajectory groups for binge drinking (none vs. any), marijuana (none/infrequent vs. daily), and recreational drug use (none vs. any). Binge drinking and recreational drug use decreased at the beginning of the pandemic. Generalized linear mixed model supported these trends. Consistent with prior research, male sex and having depressive symptoms early pandemic were positively associated with each substance use outcomes. Social support was inversely associated with recreational drug use. Conclusions: Contrary to hypotheses, problematic substance use behaviors decreased from pre-pandemic to the post-pandemic follow-up in our sample of PLHIV. Ongoing surveillance is needed to assess whether this pattern persists as the pandemic continues. Highlights: COVID-19 pandemic control efforts may shape PLHIV's substance use trajectories. Binge alcohol consumption decreased at the start of COVID among PLHIV. Recreational drug use decreased at the start of COVID among PLHIV. Depressive symptoms were positively linked to substance use trajectories in PLHIV. Functional social support was protective against PLHIV's recreational drug use.